If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2a + -9 = 3 Reorder the terms: -9 + -2a = 3 Solving -9 + -2a = 3 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -2a = 3 + 9 Combine like terms: -9 + 9 = 0 0 + -2a = 3 + 9 -2a = 3 + 9 Combine like terms: 3 + 9 = 12 -2a = 12 Divide each side by '-2'. a = -6 Simplifying a = -6
| x-4sqrtx-12=o | | 0.4x+2.5=3.9+1.3x | | -2+11=12x-5-11x | | y+22*7+y+44*4=11 | | n(s)=0.005s^2+0.007s-0.031 | | 20+5u+10u-20-14u=1u | | Y=-6(3) | | 12.5k=17.5 | | 4-4sin(5)= | | 23=0.6h-7 | | 3n^2-9n-120= | | 9x+4y=-18 | | Y=-6(-2) | | -10=x-a | | (10/x)+3=(x+9/x-4) | | 2y^2+y+21=0 | | v=yns | | 8+6x+4x+2=180 | | 3a+2b-3a= | | 2p^2=94-16p | | 8+6x+4x+2=1i | | .15x+20=.25+5x | | 18+0.8b=50 | | 2x+105=6x+41 | | 3-3*4= | | 8-2(8-5x)=0 | | 19-4h=1-5h | | sqrt(9x+108)=2x+22 | | -2(-4)+5y=18 | | 11x-(2x-9)=45 | | 4d+8=12 | | 0.4x-2.5=3.9+1.3x |